1) \(-6x^2-x+7=0\)
\(\Leftrightarrow-6x^2+6x-7x+7=0\)
\(\Leftrightarrow\left(-6x^2+6x\right)-\left(7x-7\right)=0\)
\(\Leftrightarrow-6x\left(x-1\right)-7\left(x-1\right)=0\)
\(\Leftrightarrow\left(-6x-7\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}-6x-7=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{7}{6}\\x=1\end{matrix}\right.\)
2) \(-4x^2-5x+9=0\)
\(\Leftrightarrow-4x^2+4x-9x+9=0\)
\(\Leftrightarrow\left(-4x^2+4x\right)-\left(9x-9\right)=0\)
\(\Leftrightarrow-4x\left(x-1\right)-9\left(x-1\right)=0\)
\(\Leftrightarrow\left(-4x-9\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}-4x-9=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{9}{4}\\x=1\end{matrix}\right.\)
3) \(x^2+3x-4=0\)
\(\Leftrightarrow x^2-x+4x-4=0\)
\(\Leftrightarrow\left(x^2-x\right)+\left(4x-4\right)=0\)
\(\Leftrightarrow x\left(x-1\right)+4\left(x-1\right)=0\)
\(\Leftrightarrow\left(x+4\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+4=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-4\\x=1\end{matrix}\right.\)
4) \(x^2-6x-7=0\)
\(\Leftrightarrow x^2+x-7x-7=0\)
\(\Leftrightarrow\left(x^2+x\right)-\left(7x+7\right)=0\)
\(\Leftrightarrow x\left(x+1\right)-7\left(x+1\right)=0\)
\(\Leftrightarrow\left(x-7\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-7=0\\x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=7\\x=-1\end{matrix}\right.\)
5) \(x^2+5x+4=0\)
\(\Leftrightarrow x^2+x+4x+4=0\)
\(\Leftrightarrow\left(x^2+x\right)+\left(4x+4\right)=0\)
\(\Leftrightarrow x\left(x+1\right)+4\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+4\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+4=0\\x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-4\\x=-1\end{matrix}\right.\)
a) \(-6x^2-x+7=0\)
\(\Leftrightarrow-6x^2+6x-7x+7=0\)
\(\Leftrightarrow-6x\left(x-1\right)-7\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(-6x-7\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{-7}{6}\end{matrix}\right.\)
b) \(-4x^2-5x+9=0\)
\(\Leftrightarrow-4x^2+4x-9x+9=0\)
\(\Leftrightarrow-4x\left(x-1\right)-9\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(-4x-9\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-2,25\end{matrix}\right.\)
c) \(x^2+3x-4=0\)
\(\Leftrightarrow x^2-x+4x-4=0\)
\(\Leftrightarrow x\left(x-1\right)+4\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-4\end{matrix}\right.\)
d) \(x^2-6x-7=0\)
\(\Leftrightarrow x^2+x-7x-7=0\)
\(\Leftrightarrow x\left(x+1\right)-7\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x-7\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=7\end{matrix}\right.\)
e) \(x^2+5x+4=0\)
\(\Leftrightarrow x^2+x+4x+4=0\)
\(\Leftrightarrow x\left(x+1\right)+4\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=-4\end{matrix}\right.\)
1/
x=1;x=\(-\dfrac{7}{6}\)
2/
x=1;x=\(-\dfrac{9}{4}\)
3/
x=1;x=-1
4/
x=7;x=-1
5/
x=-1;x=-4
GIẢI RA LẢN LẮM!!